Organizational Support Moderates the Effect of Knowledge Management on Organizational Performance - Mardan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study examines the influence of knowledge management and talent management on organizational performance, while analyzing the moderating role of organizational support. The research was conducted among 168 lecturers from private universities in Kendari City, Indonesia, using a quantitative approach. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The results demonstrate that both knowledge management and talent management significantly enhance organizational performance. Furthermore, organizational support was found to significantly moderate the effect of both knowledge management and talent management on performance, strengthening their impact. These findings highlight the strategic importance of effective knowledge and talent management, particularly when supported by a strong organizational environment. This study contributes to the literature on organizational development in higher education and offers practical implications for university management aiming to optimize institutional performance through human capital strategies and supportive organizational frameworks.